Developing and implementing a coaching philosophy: Guidance from award-winning strength and conditioning coaches - Gillham, A.; Schofield, G.; Doscher, M.; Dalrymple, D.; Kenn, J. (International Sport Coaching Journal, 2016)
Traditional examinations of coaching philosophies consider the perspective of sport coaches (e.g., soccer, cricket, rugby). The focus on sport coaches` coaching philosophy has advanced the study of coaching effectiveness while simultaneously omitting strength and conditioning coaches from the larger body of literature on coaching philosophy. The purpose of this paper is to reveal how award winning strength and conditioning coaches shape and use their coaching philosophy. The participants include four renowned strength and conditioning coaches, one at the high school, one at the college, and two at the professional level. A summary is provided at the end that examines commonalities (e.g., all the respondents expressed the need to have a specific coaching philosophy) and differences (e.g., how discipline factors into their coaching philosophy) across the respondents` views and connects their viewpoints to the broader literature on sport coaching.